INTERACTIVE METHODS OF TEACHING RUSSIAN TO STUDENTS OF NON-LINGUISTIC UNIVERSITIES (Web of Teachers: Inderscience Research, 2026)
This article examines the specific features and application of interactive methods for teaching foreign languages in higher education institutions. It also explores the feasibility of using interactive methods such as "Brownian Movement," which can make lessons more diverse, enabling students to demonstrate verbal independence, and develop their communication and speaking skills.